Micronutrients in polycystic ovary syndrome: molecular pathways, deficiencies, and therapeutic potential - Natarajan, Madhumitha; E., Shweatha H.; Nataraj, Raghu (Frontiers in Endocrinology, 2026)
Polycystic Ovary Syndrome (PCOS) represents a complex endocrine–metabolic condition which presents with hyperandrogenism and anovulation together with insulin resistance and chronic low-grade inflammation affecting 21% of women during their reproductive years globally. Nutrition has always played a pivotal role in managing PCOS. Emerging evidence demonstrates that micronutrients play an essential part in regulating molecular processes that drive the pathophysiology of PCOS. The deficiency of micronutrients exacerbates insulin resistance, oxidative stress and hormonal dysregulation through their negative impact on PI3K/Akt, NF-κB and Nrf2 and steroidogenic enzyme signaling pathways, all of which play a key role in the pathophysiology of PCOS. This review synthesizes a comprehensive analysis of scientific findings which demonstrate how micronutrient levels influence the regulation of insulin function, inflammatory reactions, oxidative balance, methylation activities and ovarian health in PCOS patients. It also evaluates the potential advantages of targeted micronutrient supplementation used alongside standard management strategies, considering factors such as bioavailability and nutrigenomics, while emphasizing the need for robust large-scale randomized clinical trials. Overall, a molecularly targeted approach to micronutrients represents an emerging precision-nutrition strategy aimed at improving metabolic, reproductive, and inflammatory outcomes in women with PCOS.